Avaliação do uso de sistemas de wetlands construídas no tratamento de esgotos sanitários - Mello, Débora de (2016)
The behavior of different configurations of constructed wetlands was evaluated in the removal of carbonaceous, nitrogenous and phosphorous matter of sanitary sewage. There treatment systems were set up in rectangular box of polypropylene with 55 cm of width, 95 cm of length and 58 cm of height (each) with total volume of 0.10 m3. The systems were operated with hydraulic retention time (HRT) of 24 h, 48 h and 72h and kept at room temperature. These were classified as constructed wetlands system (CWS 1) filled with sand, gravel and seedlings of aquatic macrophyte (Eichhornia crassipes), constructed wetlands system (CWS 2) filled with sand and gravel (control) and free-water-surface (FWS) with macrophyte seedlings in the sanitary sewage. The physical-chemical characterization of the support materials was carried out with determination of pH, bulk density, relative density, moisture content, ash content and particle size. The parameters pH, liquid temperature, chemical oxygen demand (COD), total phosphorus, total Kjeldahl nitrogen (TKN), ammonia nitrogen, nitrite, nitrate, total and total suspended solids were measured in samples of the influent and effluent of each system. In the macrophyte growth and composition survey, the length and width of each individual were measured and phosphorus and total nitrogen in the plant tissue were determined. Samples of gravel and sand were collect from the systems to determine the concentrations of total and total volatile solids in the biofilm formed in the support materials. Analysis of macrophyte biomass for incorporation into concrete blocks were also performed. In the characterization of supported materials it was observed that the same are consistent with recommended for this type of treatment. The affluent used in feeding the SWCs was characterized as sewage and classified as weak to COD and TSS and medium to ST. The best efficiency for phosphorus, ammonia nitrogen and NTK was obtained in 38% SLL (HRT of 72 hours), 35% (HDT of 48 h) and 47% (HDT 72h), respectively. To the best COD removal efficiency was observed in the SWC 2 to 80% in the HDT 48 h. The results NTK absorption and total phosphorus by Eichhornia crassipes, macrophytes have shown that absorptive capacity of these nutrients. In phosphorus absorption, the SLL had a higher percentage of incorporation by 1.56% in the plant TDH 72 h (135 th day), coinciding with the TDH best removal efficiency obtained in the physical and chemical analysis of 38%. The best result of the percentage of incorporation of vegetable fiber macrophyte in concrete blocks was 2%.